Assessing soil physical properties for diverse and standard pastures under regenerative and contemporary grazing management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science, Agricultural Science at Massey University, Manawatū, Palmerston North, New Zealand - Ma, Yuehui (Emily) (Massey University, 2025)
This thesis investigates the influence of pasture type and management practices on soil physical properties within New Zealand's agricultural systems, focusing on the Whenua Haumanu Programme (WHP) at Massey University's Dairy Farm One and Pasture Crop Research Unit (PCRU). WHP is a seven-year trial aiming to assess the suitability and relevance of regenerative agriculture to New Zealand, taking our climate, soils and management systems into consideration. WHP explores contemporary and regenerative farming practices across both standard (ryegrass and white clover) and diverse pastures (multi species of grasses, herbs and legumes). This master’s thesis presents two key research chapters. Chapter 3 outlines 2023-2024 baseline soil physics data for WHP, to support ongoing and future annual comparisons to test whether there are any differences in soil physical properties between standard and diverse pastures or contemporary and regenerative grazing managements. Results to date demonstrate that no statistically significant differences exist between the treatments. Significant differences are found between soil types, reflecting natural differences in soil texture. Differences are also observed between sampling years and can be attributed to changes in moisture content. Chapter 4 investigates the short-term impact of dairy cattle grazing on soil physical properties under two contrasting management systems at Massey University’s Dairy Farm One. Soil physical properties were measured for a regeneratively managed diverse pasture and a contemporary management standard pasture before and after a grazing event under saturated spring 2024 conditions. Both paddocks displayed compaction with distinct spatial patterns linked to daily rainfall and the location of water troughs and shelter belts. High pre grazing pasture covers also appear to be linked with less treading damage, however, further analyses is required to confirm any potential trends.
Keywords: Soil Physical Properties; Regenerative Agriculture; Pasture Management; Bulk Density; Soil Penetration Resistance; Volumetric Water Content (VWC); Diverse Pastures; Contemporary Management; Grazing Practices; Soil Compaction; 410605 Soil physics; 300403 Agronomy